2016
DOI: 10.1017/s175173111500275x
|View full text |Cite
|
Sign up to set email alerts
|

Addition of crude glycerin to pig diets: sow and litter performance, and metabolic and feed intake regulating hormones

Abstract: The continued growth in biofuel production has led to a search for alternative value-added applications of its main by-product, crude glycerin. The surplus glycerin production and a higher cost of feedstuffs have increased the emphasis on evaluating its nutritive value for animal feeding. The aim of this research was to evaluate the effect of the dietary addition of crude glycerin on sow and litter performance, and to determine the serum concentrations of hormones related to energy metabolism and feed intake i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
(44 reference statements)
0
4
0
Order By: Relevance
“…In a previous work [ 42 ], it was found that there was a a tendency for higher acyl-ghrelin levels in Iberian crossbred pigs from 50 to 100 kg BW fed 10% glycerin, which were associated with a higher feed intake. In addition, pregnant sows fed diets containing glycerin (up to 6%) had lower concentrations of acyl-ghrelin and higher concentrations of leptin at 0 minutes after feeding [ 48 ] suggesting that the dietary supplementation of glycerin may have exerted a satiating effect. However, to our knowledge, the effect of glycerin inclusion on the serum concentration of ghrelin has never been previously described in piglets and requires further research.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous work [ 42 ], it was found that there was a a tendency for higher acyl-ghrelin levels in Iberian crossbred pigs from 50 to 100 kg BW fed 10% glycerin, which were associated with a higher feed intake. In addition, pregnant sows fed diets containing glycerin (up to 6%) had lower concentrations of acyl-ghrelin and higher concentrations of leptin at 0 minutes after feeding [ 48 ] suggesting that the dietary supplementation of glycerin may have exerted a satiating effect. However, to our knowledge, the effect of glycerin inclusion on the serum concentration of ghrelin has never been previously described in piglets and requires further research.…”
Section: Discussionmentioning
confidence: 99%
“…Crude glycerin has been used as an energy source to replace cereals in animal diets, thus increasing the supply of raw materials while reducing production costs [ 23 , 24 , 25 ]. Numerous studies have been performed using glycerin in diets at different stages of pig production: in sows [ 5 , 26 ], weaning pigs [ 2 , 9 , 27 ], growing and finishing pigs [ 4 , 28 ]. All of them were carried out with conventional pig genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…The main by-product of the biodiesel industry is crude glycerin, which represents approximately 10% of the biodiesel produced [1]. Crude glycerin has become a potential alternative feed ingredient for livestock in many species including poultry [2], swine [3], cattle [4,5] and small ruminants [6,7].…”
Section: Introductionmentioning
confidence: 99%